Drawing on Strategic Management Approaches to Inform Nutrition Policy Design: An Applied Policy Analysis for Salt Reduction in Packaged Foods - Helen Trevena; Bruce Neal; Shauna M. Downs; Teresa Davis; Gary Sacks; Michelle Crino; Anne Marie Thow (Kerman University of Medical Sciences, 2021)
BackgroundNutrition policies to improve the food environment frequently rely on voluntary business action for implementation, many have had mixed success. The aims of this study were to identify key food system drivers influencing the Australian packaged food sector and analyse how these might impact the willingness of food companies to voluntarily reduce salt in packaged foods. MethodsBusiness methods formed the basis of this retrospective applied policy analysis of voluntary salt reduction for the period 2013-2016 where the focal policy was the Australian Food and Health Dialogue (2009-2015). The analytical framework included political-legal, economic, social, technological (PEST) external drivers of the food system, and Porter's Five Forces for the competitive drivers of the food system. Documentary data identifying food system drivers affecting the Australian packaged food sector (comprised of the food processing and supermarket industries) were identified through a comprehensive search of the grey and academic literatures. ResultsThe interplay between external and competitive food system drivers created an environment in which voluntary salt reduction was found to be an uneasy fit. A high cost of doing business, soft growth, intense competition, asymmetry of power in favour of supermarkets, and marginal consumer interest in less salty food were found likely to create commercial disincentives to invest in voluntary salt reduction above more pressing commercial imperatives. Analysis of food manufacturing industries highlighted the highly contextual nature of food system drivers. Opportunities for nutrition policy included: support for 'shared value' in economic discourse; and, leveraging investor, supermarket, and the largely unrealised bargaining power of consumers. ConclusionBusiness frameworks can provide meaningful insights for nutrition policy on how food system drivers can thwart policy goals. Our analysis highlighted areas to incentivise voluntary action and illustrated the importance of political-legal, economic and consumer strategies for salt reduction.